Synthesis of Glycosides Bearing Chalcone Derivatives via Ferrier Rearrangement - Zainab, Ngaini; Dayang H., Abang Kamaluddin (Institut Kimia Malaysia, 2013)
A series of glycoside derivatives bearing chalcones moieties has been synthesized. A convenient synthetic method was performed from the reaction of 3,4,6-tri-O-acetyl-D-glucal with (E)-1-(4-alkyloxyphenyl)-3-(4-hydroxy-phenyl)prop-2-en-1-one (2a-2c) employing OC rearrangement to afford C-glycoside 4a-c over prolonged reaction times, in the presence of BF3.OEt2 as a catalyst. The compounds differ in the length of alkyl groups, CnH2n+1, where n= 7, 8 and 9.